Modernity and its representation in rural sociology - Tolentino, Lutgarda L. (2000)
Much of the research in rural sociology is done to confirm the imagery of modernity or pinpoint areas of intervention to realize such representation of modernity. Research concerns revolve around structural differentiation, characterization of farmers and rural women, diffusion of agricultural technology, and sustainable development. Nonetheless, while rural sociology concentrates its objectifying gaze mainly on modernity, it can claim with pride that it has also provided us with immense data on the characteristics of people in agriculture and the distribution of resources in that sector. Analysis of these data should help us understand the process of technological diffusion and the need to respect local people's knowledge about agricultural practices. Still, rural sociology can and must maintain its relevance by liberating itself from the discursive framework of modernity, which is Western-based. It has to consider other emerging theoretical positions such as post-structuralism, post-modernism and post-industrialism.
Keywords: Modernity; Agricultural sociology; Small-scale farmers; Sustainable development -- Philippines